2022
DOI: 10.3390/md20040234
|View full text |Cite
|
Sign up to set email alerts
|

What Was Old Is New Again: The Pennate Diatom Haslea ostrearia (Gaillon) Simonsen in the Multi-Omic Age

Abstract: The marine pennate diatom Haslea ostrearia has long been known for its characteristic blue pigment marennine, which is responsible for the greening of invertebrate gills, a natural phenomenon of great importance for the oyster industry. For two centuries, this taxon was considered unique; however, the recent description of a new blue Haslea species revealed unsuspected biodiversity. Marennine-like pigments are natural blue dyes that display various biological activities—e.g., antibacterial, antioxidant and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 179 publications
1
2
0
Order By: Relevance
“…In diatoms, the percentage of methylated cytosines varies markedly, with levels similar to what we found in P. multistriata (8.63% in Fragilariopsis cylindrus, Huff & Zilberman, 2014) but also much smaller (2.57% in Thalassiosira pseudonana (Huff & Zilberman, 2014) and 2.67% in Haslea ostrearia (Gabed et al, 2022)) or tremendously higher as for Cyclotella cryptica in which up to ~60% methylation was found (Traller et al, 2016). In agreement with what was found in other diatoms (Huff & Zilberman, 2014Traller et al, 2016Veluchamy et al, 2013, Gabed et al, 2022, most of the methylation was found in CG context while the global methylation level in CHG and CHH contexts was below 1% in all analyzed samples (Fig 2A, Table S2). About 70% of methylated CpGs were located within repeat regions, while we found only 0.8% in TSS and 0.7% in TTS (Fig 2B), and between 1 and 1.5% in genes, where some genes were found to be highly methylated.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In diatoms, the percentage of methylated cytosines varies markedly, with levels similar to what we found in P. multistriata (8.63% in Fragilariopsis cylindrus, Huff & Zilberman, 2014) but also much smaller (2.57% in Thalassiosira pseudonana (Huff & Zilberman, 2014) and 2.67% in Haslea ostrearia (Gabed et al, 2022)) or tremendously higher as for Cyclotella cryptica in which up to ~60% methylation was found (Traller et al, 2016). In agreement with what was found in other diatoms (Huff & Zilberman, 2014Traller et al, 2016Veluchamy et al, 2013, Gabed et al, 2022, most of the methylation was found in CG context while the global methylation level in CHG and CHH contexts was below 1% in all analyzed samples (Fig 2A, Table S2). About 70% of methylated CpGs were located within repeat regions, while we found only 0.8% in TSS and 0.7% in TTS (Fig 2B), and between 1 and 1.5% in genes, where some genes were found to be highly methylated.…”
Section: Resultssupporting
confidence: 84%
“…DNA methylation has previously been investigated in diatoms ( Huff & Zilberman, 2014; Traller et al, 2016; Veluchamy et al, 2013, Gabed et al, 2022, Hoguin et al, 2023 ), revealing the conservation of most of the enzymes required for the epigenetic machinery and confirming a major role of this process in the silencing of transposable elements (TEs).…”
Section: Introductionmentioning
confidence: 98%
“…H. ostrearia is a microalga complex to grow under laboratory conditions, and even after years of development, it is still a challenge to propose a protocol that allows it to grow without any bacteria [12,13,14]. Indeed, the tests previously performed in our laboratory showed that, even with all the nutrients needed, a high amount of antibiotics or a long exposure to them tended to kill the microalgae culture itself.…”
Section: Discussionmentioning
confidence: 99%